A critical review of energy retrofitting trends in residential buildings with particular focus on the GCC countries. (July 2021) - Ahmed, Wahhaj; Asif, Muhammad
Abstract: The building sector is a major contributor towards climate change. Within it, almost a quarter of the global electricity is consumed in the residential sector. The case for residential sector in the Gulf Cooperative Council (GCC) countries is even more critical as compared with the developed world. The per capita electricity usage in the GCC countries is among the highest globally. This indicates a necessity for these countries to improve the energy performance of buildings. Existing residential buildings make the bulk of the total building stock, and thus have a critical role in the overall performance of the building sector. It is, therefore, important for them to invest in the energy retrofitting of existing unsustainable residential buildings. The aim of this study is to present a comprehensive critical review of literature of residential buildings' energy retrofitting trends in the GCC countries. An extensive keyword based search was carried out to identify the studies under the subject area in the region. A total of 40 relevant studies were accumulated which were then critically analysed and benchmarked against global retrofit studies' trends to identify gaps in literature. It is observed that there is a lack of top-down and bottom-up physical approaches in energy retrofit studies. In addition, modern design and application tools, such as BIM, have not been applied in any study. Furthermore, no work presents a measured and verified case study of an implemented energy retrofitting project. Recommendations are also made for future studies to bridge the gap in existing literature. Highlights: A comprehensive review of literature on residential buildings' energy retrofitting trends in the GCC countries is presented. 40 relevant studies are analysed using four parameters: approach of study, pre- and post-retrofit M&V, number and type of EEMs, and software used. Gaps in literature include lack of studies utilizing: top-down and bottom-up physical approaches, BIM-based frameworks, and M&V protocols. Recommendation are made for future studies to bridge the gap in existing literature.